Medicinal plants used against gastrointestinal disorders by the Tamang people in Rasuwa district, central Nepal - Yadav, Saroj; Rajbhandary, Sangeeta (Botanica Orientalis: Journal of Plant Science, 2016)
The different ethnic groups dwelling in different phytogeographic belts of Nepal have their own traditional system of knowledge on application of plant resources for health care. The traditional knowledge of using plants is passed on from generation to generation as folklore. Rasuwa district is rich in variety of flora especially medicinal plants and ethnic people (mainly Tamang) are familiar with medicinal resources and possess rich ethno-pharmacological knowledge. These resources provide huge opportunities for community development and livelihood improvement. This paper will present the documentation of medicinal plant used for gastrointestinal disorders in Chilime, Gatlang and Thuman Village Development Committees in Rasuwa district, north-central Nepal. Botanica Orientalis – Journal of Plant Science (2016) 10: 19–23